Recreation, event, and tourism businesses : start-up and sustainable operations - Pfister, Robert E.; Tierney, Patrick T. (IL, 2009)
Recreation, Event, and Tourism Businesses: Start-Up and Sustainable Operations reveals the keys to business success in the commercial recreation, event, and tourism sector. Until now, students, professors, and professionals interested in this growing industry have been limited to general business or basic recreation texts. In this book the authors have combined their expertise as both business owners and professors to offer a comprehensive and industry-specific course textbook and step-by-step guide for business start-up. Recreation, Event, and Tourism Businesses presents new professionals and potential business owners with clear, easy-to-read directions for developing and writing a business plan. The book's business profiles and case studies serve as examples to follow when working on the plan and help readers gain insight into how businesses are planned, started, and funded. It also lays out important strategies for starting a business and shares best practices based on successful recreation businesses.
Keywords: Recreation industry- Managment; Tourism- Management